Chronic Effects of Petroleum Hydrocarbons in Tunis-Navigation Channel On Phase I and II Biotransformation Enzymes in Bivalve Species - Chalghmi H.; Zrafi I.; Saidane-Mosbahi D. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
In the present study, the contamination state by hydrocarbons in Tunis-navigation channel was assessed and biotransformation biomarker responses in the clam Ruditapes decussatus were monitored. Sediments and clams R. decussatus samples were collected from the navigation channel of Tunis during four seasons. Total hydrocarbons (TH) were extracted from clam tissues and sediments and fractionated into non-aromatic hydrocarbons (NAH) and aromatic hydrocarbons (AH). In parallel to chemical analysis, benzo[a]pyrene hydroxylase (BPH) and glutathione S-transferase (GST) activities were measured in the digestive gland of the animal during four seasons. The results showed that the NAH and AH levels in the Tunis-navigation channel are higher than those recorded in the reference site (Louza). Moreover, hydrocarbon levels vary between seasons and reach their maximum in summer and spring. For biochemical analysis, we recorded a significant increase in BPH and GST activities compared with control clams. The biomarker responses (BPH and GST) fluctuate over time. In conclusion, results confirm a state of chronic pollution by petroleum hydrocarbons in the navigation channel affecting the biotic community and can have dangerous effect on human health.